Development of a method for experimental investigation of combustion process in lean burn gas engines - Shvydkyy, Dmytro (Eastern-European Journal of Enterprise Technologies, 2018)
The problems of engine experiments in the conditions of unstable combustion were considered. A practical problem was the experimental study of the influence of spark discharge parameters of the ignition system on the operation of the gas engine at the lean limit. The possibility of expanding the lean limits by applying a high-energy capacitor discharge spark ignition system under the condition of limited erosion rate of the spark plug electrode surface was investigated. Particular attention was paid to the instability of the spark discharge as a process of transferring a portion of energy to the mixture in order to develop a flame kernel. After analyzing the results of the experiment, its significant shortcomings associated with the lack of consideration of the phenomenon of cyclic instability of pocesses before ignition of mixture – for example, the spark discharge at the spark plug electrodes were revealed. This fact led to a thorough revision of the experimental research method and formulation of technical requirements to the measuring equipment. A new method of bench tests by applying the latest automated system for the cycle-by-cycle measurement of spark discharge parameters with simultaneous processing of recorded indicator diagrams and statistical analysis of results for the last 1,000 engine cycles was proposed. The main advantage of the method is an increased reliability of the results of the experiment on the lean burn gas engine and reduction of the time for finding experimental errors. Given that this method can be implemented only in a specialized measurement system, functional requirements as part of technical specifications for developing a new measuring system were formed. The results obtained can be used in the experimental studies of combustion in lean burn gas engines at the stage of experiment planning and selection of measuring equipment.